2020
DOI: 10.5210/fm.v25i5.10116
|View full text |Cite
|
Sign up to set email alerts
|

The management of visibility in digital diplomacy: Infrastructures and techniques

Abstract: The proliferation of new media has been hailed by academics and practitioners worldwide as a revolution in the conduct of international relations, with dialogical, reconciliatory, and democratizing potentials. Several years later, however, the evidence for such progressive potentialities is scarce. To better understand the actualized role of social media in international politics and deepen our understanding of the potentialities for progressive politics online, this article examines several examples of digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Keywords can be seen as ‘visibility catalysts’ (Tsinovoi, 2020) in Google's search engine, and metrics evaluating search queries can thus be indicative of broader social and political dynamics mediated by the platform, relevant for controversy mapping. In particular we found that keyword metrics about cost 6 , competition and related searches can serve as initial entry points for repurposing Google Ads.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords can be seen as ‘visibility catalysts’ (Tsinovoi, 2020) in Google's search engine, and metrics evaluating search queries can thus be indicative of broader social and political dynamics mediated by the platform, relevant for controversy mapping. In particular we found that keyword metrics about cost 6 , competition and related searches can serve as initial entry points for repurposing Google Ads.…”
Section: Introductionmentioning
confidence: 99%